Legal Consequences of Negligence Committed by Traditional Health Workers - Savitri, Pande Luh Made Devi; Widiatedja, I Gusti Ngurah Parikesit (Syntax Corporation Indonesia, 2024)
As stated in the 1945 Constitution of the Republic of Indonesia, health is a human right and is a component of welfare that must be realized following with Pancasila and the ideals of the Indonesian nation. To be healthy, people not only trust medical health services, but also traditional medicine such as shamans, acupuncturists, healers, and others. This research is a type of normative legal research. This research collects data through relevant literature research. The Indonesian Central Statistics Agency (BPS) describes the percentage of use of traditional medicine from year to year, namely, traditional medicine used in 2011 was 23.63 percent, in 2014 was 20.99 percent and in 2023 it was 27.57 percent. This shows that public interest in traditional medicine is relatively high. The results of the discussion showed that the legal consequences obtained due to negligence committed by Traditional Health Workers in accordance with the Government Regulation of the Republic of Indonesia Number 103 of 2014 received administrative sanctions and were also based on the Criminal Code, so the negligence caused could be held accountable by the district in accordance with the provisions Article 205 of the Criminal Code and Article 343 of Law 1/2023 Article 359 of the Criminal Code and Article 474 paragraph (3).